Prime Minister Decree No. 705 the year 2023,issuing the executive regulations of the hotel and tourist establishments law promulgated by law no.8 of the year 2022 = قرار رئيس مجلس الوزراء رقم 705 لسنة 2023 بإصدار اللائحة التنفيذية لقانون المنشآت الفندقية والسياحية الصادر بقانون رقم 8 لسنة 2022 Prime Minister. - Egypt. Prime Minister. (2025)
Prime minister decree no. 705 of the year 2023 issuing the executive regulations of the hotel and tourist establishments law promulgated by law no. 8 of the year 2022 – part 1: general provisions – part 2: licensing procedures – part 3: accreditation offices – part 4: miscellaneous قرار رئيس مجلس الوزراء رقم 705 لسنة 2023 بإصدار اللائحة التنفيذية لقانون المنشآت الفندقية والسياحية الصادر بالقانون رقم 8 لسنة 2022 – الباب الأول أحكام عامة – الباب الثانى إجراءات الترخيص – الباب الثالث مكاتب الاعتماد – الباب الرابع أحكام متنوعة